The analytical marketer : how to transform your marketing organization - Sweetwood, Adele, ....- (Boston (Mass.) : Harvard Business Review Press, 2016)
Analytics are driving big changes, not only in what marketing departments do but in how they are organized, staffed, led, and run. Leaders are grappling with issues that range from building an analytically driven marketing organization and determining the kinds of structure and talent that are needed, to leading interactions with IT, finance, and sales and creating a unified view of the customer. The Analytical Marketer provides critical insight into the changing marketing organization--digital, agile, and analytical--and the tools for reinventing it. Written by the senior global vice president of marketing for SAS, The Analytical Marketer is based on firsthand experience. Challenged to change by its company's own analytical products, the SAS marketing organization was forced to rethink itself in order to take advantage of the new capabilities that those tools offer the modern marketer. Key marketers and managers at SAS tell their stories alongside the author's candid lessons learned as she led the marketing organization's transformation. With additional examples from other leading companies, this book is a practical guide to creating a set of best practices and a new marketing culture that thrives on and adds value through data and analytics.--
Introduction: Reinventing the marketing organization in the analytical era -- The customer decision journey has changed -- Adopting an analytical mindset -- Realigning your structure -- Building talent & skills -- Leading the analytical organization -- Conclusion: What's next? Your call to action.
Includes index.
Keywords: Marketing -- Technological innovations; Marketing -- Management; Quantitative research; Marketing -- Management; Marketing -- Technological innovations; Quantitative research